2020
DOI: 10.1001/jamaneurol.2020.2703
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Neurotoxicity After Chimeric Antigen Receptor T-Cell Therapy

Abstract: IMPORTANCE Chimeric antigen receptor (CAR) T-cell therapy for relapsed or refractory hematologic malignant neoplasm causes severe neurologic adverse events ranging from encephalopathy and aphasia to cerebral edema and death. The cause of neurotoxicity is incompletely understood, and its unpredictability is a reason for prolonged hospitalization after CAR T-cell infusion.OBJECTIVE To identify clinical and laboratory parameters predictive of neurotoxicity and to develop a prognostic score associated with its ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…2,5,7,8 Likewise, CRP and ferritin levels measured on the day of CAR-T-cell infusion or shortly thereafter were also associated with increased risk of severe CRS and ICANS. 1,5,6 Time (days) In preclinical models, the development of CRS has been shown to be secondary to both CAR T-cell expansion and to subsequent activation of the immune microenvironment, leading to a cytokine storm, including peak levels of in IL-1, IL-6, and other proinflammatory molecules. 19,20 Of interest, in patient-derived samples, 4 these chemokine levels associated not only with higher CAR-T-cell expansion, but also with endothelial activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5,7,8 Likewise, CRP and ferritin levels measured on the day of CAR-T-cell infusion or shortly thereafter were also associated with increased risk of severe CRS and ICANS. 1,5,6 Time (days) In preclinical models, the development of CRS has been shown to be secondary to both CAR T-cell expansion and to subsequent activation of the immune microenvironment, leading to a cytokine storm, including peak levels of in IL-1, IL-6, and other proinflammatory molecules. 19,20 Of interest, in patient-derived samples, 4 these chemokine levels associated not only with higher CAR-T-cell expansion, but also with endothelial activation.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reported on several biomarkers, including lactate dehydrogenase (LDH), as the surrogate marker of tumor burden, and C-reactive protein (CRP) and ferritin as general inflammatory markers, all 3 of whichare associated with severe CRS and/or ICANS. 2,[4][5][6][7][8] However, their individual predictive power is limited, and novel biomarkers are strongly needed.…”
Section: Introductionmentioning
confidence: 99%
“…Patients underwent leukapheresis with optional bridging therapy, followed by conditioning chemotherapy (cyclophosphamide 500 mg/m 2 /day; fludarabine 30 mg/m 2 /day) on days −5 to −3, as previously reported. 4 KTE-X19 was infused at a target dose of 2×10 6 CAR T cells/kg on day 0. 4 CRS was graded per Lee et al 15 National Cancer Institute Common Terminology Criteria for Adverse Events, V.4.03, was used to grade the severity of adverse events, including NE and symptoms of CRS.…”
Section: Methodsmentioning
confidence: 99%
“…Lately, Rubin et al developed a model for predicting neurotoxicity after anti-CD19 CAR T cell therapy with axicabtagene ciloleucel for RR NHL. In this scoring system, the following factors were considered: age (≥52 versus <52 years), maximum CRP (≥8.95 versus <8.95 mg/dl), maximum ferritin (≥641 versus <641 ng/ml), minimum white blood cell (WBC) count (<790 versus ≥790/ml), time point of CRS onset (prior to versus after day 3), histologic subtype of lymphoma (aggressive versus indolent), temperature (≥38.5°C versus <38.5°C), presence of CRS of any grade, and use of tocilizumab prior to day 5 (105). This is a valuable instrument for triaging and resource allocation, and development of such a predictive model for MM patients is highly warranted.…”
Section: Immune Effector Cell-associated Neurotoxicity Syndromementioning
confidence: 99%